PRESERVATION AND MODELLING FORM OF KUTAI ORIGINAL HOUSE TO MAINTAIN TRADITIONAL ARCHITECTURE - Hatta Musthafa Aham Putra; Nur Husniah Thamrin (Jurnal Arsitektur ARCADE, 2020)
Abstract: The traditional house of Kutai is one of the traditional houses located in the region of Kutai Kartanegara, East Borneo, which is currently almost extinct in population. Various houses have adapted to changes in physical shape due to the impact of technology and the needs of their residents. If this problem is not immediately concerned, there is a tendency to be more difficult to recognize the characteristics and character of the Kutai traditional house. The architectural character of the Kutai traditional house including to the structure and construction system used, building materials, cultural ornaments attached to the outside and inside of the building, and the colors. This research is directed to get the formulation of the architectural character of the Kutai traditional house. It is urgent to conserve the Kutai House‘s identity in the future, by considering to preserve the existence and the uniqueness of these traditional building. Keyword: Kutai Architecture, Kutai House, Kutai Traditional House Abstrak: Rumah adat Kutai merupakan salah satu rumah adat yang berlokasi di wilayah Kutai Kartanegara, Kalimantan Timur, yang saat ini telah hampir punah populasinya. Berbagai rumah telah beradaptasi dengan perubahan bentuk fisik dikarenakan dampak teknologi dan kebutuhan penghuninya. Apabila hal ini tidak segera diperhatikan, ada kecenderungan akan lebih sulit mengenali ciri khas dan karakter rumah adat Kutai tersebut. Karakter arsitektur tersebut berupa ruang-ruang pada bangunan rumah adat Kutai, sistem struktur dan konstruksi yang digunakan, material bangunan, ornamen budaya yang melekat pada luar maupun dalam bangunan, hingga warna-warna. Penelitian ini difokuskan untuk mendapatkan rumusan karakter bentuk dari rumah tradisional Kutai. Hal penting yang menjadi tujuan dari penelitian ini adalah untuk menjaga keberadaan dan keunikan dari bangunan Rumah Tradisional Kutai.Kata Kunci: Arsitektur Kutai, Rumah Kutai, Rumah Tradisional Kutai